Financial Capability of Accounting Students in South African Universities - Nomlala, Bomi; Sibanda, Mabutho (Journal of Reviews on Global Economics, 2020)
This study surveyed 1582 students studying Accounting degrees at universities in South Africa to assess their financial capability levels and intra-component drivers of financial capability. The study utilised statistical methods such as structural equation modelling technique was used to determine drivers of financial capability; regression analysis was further done to examine relationships between the students’ mean percentage scores and their socio-demographic factors. The findings of the study suggest that accounting students are highly financially capable. It was further found that financial capability is driven by financial attitude; financial behaviour, and numeracy skills of the accounting students. In addition, the study found education, level of study, and race as statistically significant and socio-demographic influences of financial capability. This study suggests that financial capability can be further improved via improvements in financial attitude, financial behaviour, numeracy skills and education among racial groups in South Africa.